2018
DOI: 10.1002/jcb.28170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catalpol on bronchial asthma and its relationship with cytokines

Abstract: An animal (BALB/c mice) model of catalpol associated with bronchial asthma in vivo was established, and the effects of catalpol and its relationship with cytokines were investigated. A total of 30 adult BALB/c mice were randomly divided into a positive control group, a model group, and a catalpol group, with 10 mice in each group. The lung function of mice, the cell count, and the cytokine concentrations in bronchoalveolar lavage fluid (BALF) were detected.The levels of cytokines [interleukin 4 (IL-4), interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Some of its anti-inflammatory potential has been also discussed later sections, for example in the context of neurodegenerative, cardiovascular disorders, cancer and in hepatoprotective effect (Section 3, Section 5, Section 6, and Section 7.1). The anti-inflammatory potential of catalpol had also been reported in acute pancreatitis, hyperhomocysteinemia, diabetic complications, acute lung injury, multiple sclerosis, and various lipopolysaccharide (LPS)-induced inflammatory models [9][10][11][12]. The anti-inflammatory and antioxidant effects of catalpol are summarized in Table 1.…”
Section: Effects Of Catalpol In Inflammatory and Oxidative Stress Conmentioning
confidence: 94%
“…Some of its anti-inflammatory potential has been also discussed later sections, for example in the context of neurodegenerative, cardiovascular disorders, cancer and in hepatoprotective effect (Section 3, Section 5, Section 6, and Section 7.1). The anti-inflammatory potential of catalpol had also been reported in acute pancreatitis, hyperhomocysteinemia, diabetic complications, acute lung injury, multiple sclerosis, and various lipopolysaccharide (LPS)-induced inflammatory models [9][10][11][12]. The anti-inflammatory and antioxidant effects of catalpol are summarized in Table 1.…”
Section: Effects Of Catalpol In Inflammatory and Oxidative Stress Conmentioning
confidence: 94%
“…Catalpol, a major component of Rehmanniae Radix, not only reduced transforming growth factor (TGF-β1) and epidermal growth factor (EGF), which are important factors in lung tissue damage and airway remodeling [ 52 ], but also lowered IL-4 and IL-5 and inhibited eosinophil infiltration and increase of CCL11, CCR3, and IL-5Rα in the OVA-induced asthma model [ 53 ]. In another study, catalpol showed immunomodulatory effects by reducing IL-4 and elevating decreased IFN-γ in BALF [ 54 ]. Corni Fructus has been reported to reduce IL-5, CCL11, and OVA-specific IgE and inhibit eosinophil infiltration in the OVA-induced asthma model [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, we found that DFSG contains multiple compounds and exerts multitarget effects, as it regulates the cytokines IL-12, IFN-c, IL-5, and IL-13 through the coordinated action of its various compounds [29]. e isolated ingredients of medicinal plants include steroids, flavonoids, phenylpropanoids, and alkaloids, and compounds such as catalpol [30], β-sitosterol [31], chlorogenic acid [32], oleanolic acid [33], and ursolic acid [34] exert pharmacological antiasthma, immunomodulatory, and anti-inflammatory effects, as verified using in vitro and in vivo bioassays. erefore, we identified twenty-two different chemical constituents in GSYJ (data not shown).…”
Section: Discussionmentioning
confidence: 99%